Postangioedema attack skin blisters: an unusual presentation of hereditary angioedema. (10th April 2014) - Wiesen, Jonathan; Gonzalez-Estrada, Alexei; Auron, Moises
Abstract : Hereditary angioedema (HAE) is an autosomal dominant disorder characterised by attacks of self-limited swelling affecting extremities, face and intra-abdominal organs, most often caused by mutations in the C1-inhibitor gene with secondary Bradykinin-mediated increased vascular permeability. We describe a 36-year-old man with a history of HAE who presented with painful interdigital bullae secondary to an acute oedema exacerbation. Biopsy and cultures of the lesions were negative and they resolved spontaneously. It is important to highlight and recognise the development of oedema blisters after resolution of a flare of HAE (only 1 previous case report), and hence avoid unnecessary dermatological diagnostic workup and treatment.